Effects of Sodium Fluoride on Water and Acid Secretion, Soluble Mucus and Adherent Mucus of the Rat Stomach - Kamel Gharzouli; Smain Amira; Seddik Khennouf; Akila Gharzouli (Canadian Journal of Gastroenterology)
Chronic and acute ingestion of fluoride may lead to both structural and functional alterations of the gastric mucosa. The aim of this study was to investigate the effects of sodium fluoride on gastric secretion and mucosal barrier. Filling the rat stomach for 1 h with sodium fluoride (5 and 20 mmol/L) induced an increase in fluid, fucose and galactose output. This effect was accompanied by a marked pH-dependent reduction of titratable acidity of the lumen. The amount of Alcian blue bound to adherent mucus was reduced in a pH-independent manner by sodium fluoride. The absence of a correlation between soluble glycoproteins and adherent mucus suggests that sodium fluoride does not stimulate mucus secretion, but rather acts as a barrier-breaking agent by its accumulation, together with acid, into the mucosa.